1967
DOI: 10.1002/aic.690130610
|View full text |Cite
|
Sign up to set email alerts
|

Polymer reactors and molecular weight distribution: Part II. Free radical polymerization in a batch reactor

Abstract: fhe free radical polymerization of styrene in benzene was studied theoretically and experimentally over ranges of monomer and catalyst (AIEN) concentrations and temperature in an isothermal, stirred batch reactor. Molecular weight distributions were measured with a gel permeation chromatograph. Tung's hermite polynomial method was used to correct for imperfect resolution.The differential rate equations have been solved to predict the conversion of monomer and molecular weight distribution of the polymer as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…The works of Hamielec and co-workers represent notable exceptions to the above. Using carefully controlled batch experi ments, MWD determination by gel permeation chromatography (GPC), Hamielec et al (25) obtained good agreement with theoretical calcula tions based on parameters at low viscosities. Duerksen et al (17) did the same for CSTR's.…”
Section: Reaction Mechanismsmentioning
confidence: 55%
“…The works of Hamielec and co-workers represent notable exceptions to the above. Using carefully controlled batch experi ments, MWD determination by gel permeation chromatography (GPC), Hamielec et al (25) obtained good agreement with theoretical calcula tions based on parameters at low viscosities. Duerksen et al (17) did the same for CSTR's.…”
Section: Reaction Mechanismsmentioning
confidence: 55%
“…Hamielec and coworkers [3,4] investigated, both experimentally and theoretically, the free-radical bulk and solution polymerization of styrene at different temperatures (e.g., 50-75 8C), in the presence of a chemical initiator (2,2 0 -azoisobutyronitrile, AIBN). Tefera et al [5] also investigated, both experimentally and theoretically, the free-radical suspension polymerization of styrene at different temperatures (i.e., 70, 75, and 80 8C) and initiator concentrations (i.e., AIBN: 0.15-0.45 wt.-% of styrene).…”
Section: Introductionmentioning
confidence: 99%
“…For quality control, where perturbations are very small, this is satisfactory. As a general specification this is more questionable since some properties depend more strongly on the tail of the MWD (5,6,7).…”
Section: Product Specificationsmentioning
confidence: 97%
“…Experimental runs were simulated with a selected MTD and a perfectly mixed RTD by calculating the outlet conditions-i.e., monomer concentration and the moments of the molecular weight dis tribution of polymer products. It was shown that the parameters of the MTD could be obtained from the outlet conditions of a known reactor system using the Rosenbrock pattern search method as described by Wilde (5) to minimize the deviation between the calculated sum of first three moments of the molecular weight distribution and that of the experimental values.…”
Section: = F~e(a*)c(**)damentioning
confidence: 99%